Bark beetles : biology and ecology of native and invasive species - Vega, Fernando E.; Hofstetter, Richard W. (London : Academic Press, 2015)
Bark Beetles: Biology and Ecology of Native and Invasive Species provides a thorough discussion of these economically important pests of coniferous and broadleaf trees and their importance in agriculture. It is the first book in the market solely dedicated to this important group of insects, and contains 15 chapters on natural history and ecology, morphology, taxonomy and phylogenetics, evolution and diversity, population dynamics, resistance, symbiotic associations, natural enemies, climate change, management strategies, economics, and politics, with some chapters exclusively devoted to some of the most economically important bark beetle genera, including Dendroctonus, Ips, Tomicus, Hypothenemus, and Scolytus. This text is ideal for entomology and forestry courses, and is aimed at scientists, faculty members, forest managers, practitioners of biological control of insect pests, mycologists interested in bark beetle-fungal associations, and students in the disciplines of entomology, ecology, and forestry.
1.3.3. Phylogenetic-Pre-DNA Sequence1.3.4. Phylogenetic-Molecular and Morphological; 1.3.5. Scolytidae or Scolytinae?; 2. Current approaches and status of the field; 2.1. Morphological Approaches; 2.1.1. Morphological Approaches: Improvements in Imaging; 2.1.2. Current Electronic Image Depositories; 2.2. Molecular Approaches: DNA Sequences in Phylogenetic Analyses; 2.2.1. Limitations of Marker-based Phylogenetics; 2.2.2. The Biggest Picture: Phylogenomic Data; 2.3. Species Delimitation, Population Genetics, and Phylogeography; 2.3.1. The Most Detailed Resolution: Genotyping-by-Sequencing.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed January 22, 2015).
Keywords: Bark beetles; SCIENCE -- Life Sciences -- Zoology -- General; Bark beetles; Beetles; Electronic books